Administrative Sanctions Against BPJS Kesehatan Independent Membership Reviewed from a Human Rights Perspective - Lusy Erawati (Jurnal Indonesia Sosial Teknologi, 2024)
Health services, obtaining social security, and public services are human rights of all Indonesian people, and statutory regulations protect their implementation. Membership in BPJS Health is mandatory for Indonesian people. The government will give administrative sanctions through written warnings and fines and not receive certain public services to independent participants if they do not participate in the BPJS Health program. These sanctions cause certain problems because getting public services is a constitutional right of society and a very important need in society's activities to develop itself. The research method used in this research is normative juridical with a statutory and conceptual approach. The results of the analysis and discussion show that the government is responsible for providing quality health and public services to the community. Administrative sanctions for independent participants for not registering as BPJS Health members are not in line with human rights.